Novel therapeutic strategies targeting vascular redox in human atherosclerosis. - Antonopoulos, A; Antoniades, C; Tousoulis, D; Bakogiannis, C; Demosthenous, M; Psarros, C; Stefanadis, C (2009)
It is now widely accepted that redox signaling is a key feature in vascular homeostasis. Reactive oxygen species are generated by a wide range of enzymatic systems located in both vascular endothelium and vascular wall. Further, to their role as cytotoxic molecules produced by immune system, free radicals play critical signaling roles in the vascular wall. By regulating several redox-sensitive transcription pathways, free radicals play a key role in the synthesis of inflammatory mediators in both vascular endothelium and vascular wall, with important role in the overall vascular dysfunction. The well-established role of redox state in vascular disease mandates that development of newer therapeutic strategies should be able to alter redox-sensitive intracellular signaling events. Widely used cardiovascular agents like statins or angiotensin receptor blockers have well documented beneficial effects on vascular redox state, reflected also in clinical outcome improvement. Newer promising strategies along with recent patented inventions may also include thiazolidinediones, folates, tetrahydrobiopterin, cyclopentone prostaglandins and aldose reductase inhibitors with well known effects on vascular redox, but with still unclear results on clinical outcome. Better understanding of redox-sensitive intracellular signaling pathways could indicate the critical steps to intervene with newer agents to reverse vascular dysfunction, inhibiting atherosclerosis progression and potentially improve clinical outcome.